Peningkatan Pengetahuan Masyarakat Mengenai Hubungan Kesehatan Jiwa dan Aktivitas Fisik Terhadap Kesehatan Gigi dan Mulut di Desa Padang Lampe - Muhammad Alim Jaya; Muhammad Fajrin Wijaya; Muhammad Jayadi Abdi (Jurnal Pelayanan Masyarakat, 2024)
Mental health is an integral part of physical health. Mental and physical health are interrelated both directly and indirectly. A healthy soul affects how we think, feel and behave including stress. The impact of stress on dental and oral health behavior has long been discussed in the dental literature. Psychogenic components such as stress and anxiety can act as risk factors that can influence the onset of oral mucosal infections due to changes in body condition that act as risk factors that can influence the onset of disorders or problems in the oral cavity. The purpose of this community service is to increase the knowledge of the Padang Lampe Village community about the relationship between managing mental health and physical activity with maintaining dental and oral health. The method of implementing the community service is with direct counseling techniques to the community. The results of the community service, in general, the counseling participants have an increased understanding of the relationship between mental health and physical activity to dental and oral health. The conclusion of this community service is the importance of continuous education and counseling to the community regarding the importance of maintaining and preserving the soul and dental and oral health.